Investigating Novice Programming Abilities with the Help of Psychometric Assessment - Berges, Marc-Pascal (Proceedings of Society for Information Technology & Teacher Education International Conference 2015, 2015)
In 2008, a working group in the computer science department at Technische Universität München School of Education piloted an optional 2 extonehalf day experience that took place just before the first undergraduate lecture in computer science. This experimental project was a unique attempt to assess prior knowledge and programming skills for new CS students. The research team used item response theory on source code for 21 fundamental coding concepts in an attempt to assess novice programming skills. The responses were transferred to a Rasch Model which allows personal parameters to be assessed. Now that a metric has been validated for the coding ability, we are seeking to further our work by attempting to evaluate other core programming competencies. Originally, the complexity of the programming task was of central interest, we are seeking to further our work by creating a multidimensional assessment of problem solving abilities as well as coding abilities represents the different facets of